1992
DOI: 10.1677/joe.0.134r001
|View full text |Cite
|
Sign up to set email alerts
|

Elevating Maternal Insulin-Like Growth Factor-I in Mice and Rats Alters the Pattern of Fetal Growth by Removing Maternal Constraint

Abstract: Fetal growth is normally constrained by maternal factors. This constraint is demonstrated by the usual inverse linear relationship between litter size and mean fetal weight. Cross-breeding experiments between mice of lines selected for high or low plasma insulin-like growth factor (IGF-I) levels suggested that elevations in maternal IGF-I abolish (P less than 0.01) this constraining effect and reverse the usual positive relationship between fetal and placental size in late gestation. This was confirmed by trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
44
2
5

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 0 publications
5
44
2
5
Order By: Relevance
“…Studies in rats and mice (Gluckman et al, 1992) have shown that maternal IGF I affects foetal growth by altering some aspects of placental function. Unfortunately, placental production and transfer of IGF was unable to be measured in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in rats and mice (Gluckman et al, 1992) have shown that maternal IGF I affects foetal growth by altering some aspects of placental function. Unfortunately, placental production and transfer of IGF was unable to be measured in this study.…”
Section: Discussionmentioning
confidence: 99%
“…IGF I appears to be particularly sensitive to dietary protein levels during second trimester of gestation. Considering the importance of IGF concentrations in the development of the foetus (Gluckman et al, 1992;Brameld et al, 2000), these may represent one of the mechanisms by which foetal development is affected by protein levels in pasture. From our studies, the level of protein in the diet that can be produced by medic pasture is clearly sufficient to influence IGF concentrations in the heifers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PMV was resuspended in HEPES-sucrose buffer (300 mM sucrose in 10 mM HEPES-Tris-base buffer, pH 7.4) by passing it 20 times through a 25-gauge needle, It has been widely accepted that the supply of amino acids from mother to fetus is of crucial importance for fetal growth and development. In vitro study, the treatment with growth factors, such as epidermal growth factor (EGF) and insulin-like growth factor-I (IGF-I) resulted in fetal growth [3,8,10], increased amino acid uptake in cultured placental cells [15,18,21]. The serum levels of amino acid are known to be kept higher in the fetal side than those in maternal side in human [5] and also in rats [3], indicating an active transport across the placental microvillous membrane [14].…”
mentioning
confidence: 99%
“…In humans, a positive correlation between foetal IGF-I concentration at term and birth mass has been reported (Gluckman et al 1983). Similarly, in genetically divergent IGF-I lines of mice, high IGF-I line mice display heavier foetal weights (Kroonsberg et al 1989), and administration of IGF-I in pregnant mice has also been shown to remove the negative correlation between foetal weight and litter size (Gluckman et al 1992). Conversely, in sheep, divergent selection based on circulating plasma IGF-I concentrations has resulted in unexpectedly lower birth weights in the high IGF-I line in comparison to the low line (Blair et al 2002;Kenyon et al 2007).…”
Section: Introductionmentioning
confidence: 98%